ANALYSIS OF ASN BKPSDM JOB PERFORMANCE IN PLANNING AND DEVELOPING EDUCATORS AND EDUCATION PERSONNEL IN MUARO JAMBI REGENCY - Hendri Wijaya; Muhammad Imam Arifin; Eva Iryani; Mohamad Muspawi; Mulyadi (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to analyze the job performance of Civil Servants (ASN) at the Civil Service and Human Resource Development Agency (BKPSDM) of Muaro Jambi Regency in carrying out the functions of planning and developing human resources (HR) in education, particularly teachers and educational personnel. The study focuses on the effectiveness of teacher formation planning, the implementation of competency development, and the implementation of a merit system in education HR management. The research uses a descriptive qualitative approach through in-depth interviews, observation, and documentation studies. The results show that the performance of BKPSDM ASN has met education management standards in several aspects, especially in the administration of teacher requirement planning and the implementation of competency development programs. However, there are several limitations, such as gaps in the digital literacy of civil servants, suboptimal mapping of school performance-based training needs, and a lack of innovation in the implementation of educational human resource development. This study concludes that the job performance of ASN BKPSDM contributes significantly to the effectiveness of managing teaching and education personnel, but still requires systemic strengthening through data integration, competency improvement, and alignment of performance indicators with education quality standards. Keywords: Job Performance, Education Management, BKPSDM, Educators Abstrak Penelitian ini bertujuan untuk menganalisis job performance Aparatur Sipil Negara (ASN) pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Muaro Jambi dalam melaksanakan fungsi perencanaan dan pengembangan sumber daya manusia (SDM) pendidikan, khususnya guru dan tenaga kependidikan. Kajian difokuskan pada efektivitas perencanaan formasi guru, pelaksanaan pengembangan kompetensi, serta implementasi sistem merit dalam pengelolaan SDM pendidikan. Penelitian menggunakan pendekatan kualitatif deskriptif melalui teknik wawancara mendalam, observasi, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa kinerja ASN BKPSDM telah memenuhi standar manajemen pendidikan dalam beberapa aspek, terutama administrasi perencanaan kebutuhan guru dan pelaksanaan program pengembangan kompetensi. Namun demikian, terdapat beberapa keterbatasan seperti kesenjangan literasi digital aparatur, kurang optimalnya pemetaan kebutuhan pelatihan berbasis kinerja sekolah, serta minimnya inovasi dalam implementasi pengembangan SDM pendidikan. Penelitian ini menyimpulkan bahwa job performance ASN BKPSDM memberikan kontribusi signifikan terhadap efektivitas pengelolaan tenaga pendidik dan kependidikan, namun masih memerlukan penguatan sistemik melalui integrasi data, peningkatan kompetensi, dan keselarasan indikator kinerja dengan standar mutu pendidikan.